West Africa Farmers Innovation Fair FIPAO - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
Burkina Faso hosted on 15 and 16 May the Innovation Fair Farmers in West Africa (FIPAO). This event aimed to draw attention to farmer innovation and the role of peasant producers in agricultural research, and to facilitate interaction, linkages and learning between all relevant actors. It also helped promote family farming through the development of innovative farmers.